Alterations in the Intestinal Morphology, Gut Microbiota, and Trace Mineral Status Following Intraamniotic Administration (Gallus gallus) of Genistein. (7th June 2021) - Cheng, Jacquelyn; Sisser, Philip; Kolba, Nikolai; Tako, Elad
Abstract: Objectives: Assess the effects of intraamniotic genistein administration on brush border membrane (BBM) functionality, intestinal morphology, cecal microbiome and Fe status in-vivo ( Gallus gallus ). Methods: Broiler chickens ( Gallus gallus, n  = 39) were injected in ovo (day 17 of embryonic incubation) with varying concentrations of 1 mL pure genistein in 18 Ω H2 O. Two treatment groups (1.25, 2.5%), two controls (water and non-injected), and a positive control (5% inulin) were administered. Upon hatch, blood was taken for hemoglobin determination and chicks were then euthanized. Nutritional status was assessed using pectoral muscle glycogen storage and body weight analysis. Duodenal and cecal tissues were excised for BBM morphometric analysis, mRNA gene expression of relevant BBM Fe transporter proteins, and 16S rRNA gene sequencing was done to evaluate gut microbiota modulation in the intestinal cecum. Results: Preliminary results reveal significant increase in body weight, decrease of cecum weight, and increase in villus surface area with the higher dose of genistein administration ( P < 0.05) compared to controls. Blood hemoglobin was found to be increased in the genistein-treated groups when compared to the controls ( P < 0.05). Additionally, genistein administration downregulated the expression of duodenal cytochrome B (DcytB) and divalent metal transporter 1 (DMT1) and upregulated the expression of ferroportin with a dose responsive effect, indicating improved Fe physiological status. Further, administration of genistein altered the composition and function of cecal microbiota. Conclusions: Genistein is a compound present in multiple staple food crops, including soybeans and chickpeas, and may be extracted and potentially used to enhance dietary Fe bioavailability and improve Fe deficiency in vulnerable populations. Recent evidence suggests a physiological role for genistein administration in improving the functionality and development of the BBM, improving Fe status, affecting the intestinal microbiome, as well as improving physiological status. Funding Sources: N/A.